PENGAMBILAN KEPUTUSAN MENGGUNAKAN ANALISIS BIAYA DIFERENSIAL PADA USAHA ZAHRA LANGGENG KONVEKSI DAN SABLON - Y S, PRAYUDIANA Yulita (Jurnal Akuntansi AKUNESA, 2013)
The convection business is a profitable business, because of the people needs forclothing have increased all the time. However, these circumstances make thecompany confused if the order is less than or exceed the production capacity. Oneof these companies is Zahra Langgeng Konveksi dan Sablon. The purpose of thisstudy was to determine the extent of differential cost analysis influenced thedecision to accept orders. With description research trough calculating andanalyzing the simple financial notes. The author reach a conclusion that ZahraLanggeng Konveksi dan Sablon still receives a special order after the differentialprofits calculatedKeywords : convection bussiness, differential profits, special order